1996
DOI: 10.1128/jb.178.3.817-822.1996
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of immediate upshift (Iup) proteins during recovery of marine Vibrio sp. strain S14 subjected to long-term carbon starvation

Abstract: Proteins induced during the initial phase of recovery after long-term carbon starvation in the marine Vibrio sp. strain S14 were identified by two-dimensional gel electrophoresis analysis. Nutritional upshift experiments with pulse-labeled cells were performed after addition of glucose to cells starved for 48 h. Eighteen proteins synthesized during the first 3 min after substrate addition were identified and designated immediate upshift proteins (Iup proteins). They were induced at least 10-fold compared with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
28
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 33 publications
1
28
0
Order By: Relevance
“…These changes in the pattern of protein synthesis are qualitatively similar to those that occur during recovery from starvation in other gram-negative bacteria (1,7,12). Synthesis of different exponential-phase proteins is induced in a specific temporal order, and the synthesis of starvation-induced proteins stops at different times after the addition of nutrients.…”
supporting
confidence: 65%
See 1 more Smart Citation
“…These changes in the pattern of protein synthesis are qualitatively similar to those that occur during recovery from starvation in other gram-negative bacteria (1,7,12). Synthesis of different exponential-phase proteins is induced in a specific temporal order, and the synthesis of starvation-induced proteins stops at different times after the addition of nutrients.…”
supporting
confidence: 65%
“…Proteins expressed only or predominantly during outgrowth from starvation have been observed in Vibrio sp. strain S14 (1,12) and Pseudomonas putida KT2442 (7) and during outgrowth of Bacillus subtilis spores (22). These outgrowth-specific proteins are likely to be involved in recovery from starvation.…”
mentioning
confidence: 99%
“…Alternatively, transcripts and proteins might persist in the cells in inactive states for a significant period, even after dispersal into areas with low substrate concentrations. For example, stable but silent transcripts have been found in bacteria after several days of starvation (49,50). Furthermore, gene expression may not change immediately in response to external stimulus (14).…”
Section: Mrna and Protein Profilesmentioning
confidence: 99%
“…The starvation-survival strategies employed by bacteria include at least the adaptive processes of olhgotrophy, spore and cyst formation, and copiotrophy (Ostling et al, 1993;Poindexter, 1981;Rozak & Colwell, 1987;Schut et al, 1993). Copiotrophic bacteria exhibit relatively rapid growth rates under conditions of abundant nutrients and survive starvation without the development of spores or cysts (Nystrom et al, 1990 Starvation-stress in V. anguillarum Matin, 1991;Nystrom et al, 1990;Ostling et al, 1993). In other words, these bacteria survive starvation by expressing genes which enable the cells to enter a starvation-induced adaptation state, which is resistant not only to long-term starvation but also to a variety of physical and chemical stresses, and permits the cells to initiate outgrowth when nutrients are available (Marouga & Kjelleberg, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Some bacteria escape these harsh conditions by differentiating into stress-resistant forms such as endospores or myxospores (Sonenshein, 1989;Zusman, 1984). Recent investigations have demonstrated that many non-differentiating bacteria also have the ability to withstand long periods of nutrient limitation and starvation (Matin et al, 1989 ;Morita, 1993;Ostling et al, 1993;Spector & Foster, 1993). Indeed, it has been suggested that in natural environments most micro-organisms face intermittent or prolonged periods of nutrient-limiting conditions and rarely, if ever, grow at rates approaching maximum mechanisms that allow the cells to survive exposure to multiple physical stresses (Givskov et af., 1994b; Jenkins et af., 1988;Ostling et al, 1993).…”
Section: In Natural Environments Organisms Are Constantlymentioning
confidence: 99%